Effects of a New Form of Resistance-Type High-Intensity Interval Training on Cardiac Structure, Hemodynamics, and Physiological and Performance Adaptations in Well-Trained Kayak Sprint Athletes - Sheykhlouvand, Mohsen; Arazi, Hamid; Astorino, Todd A.; Suzuki, Katsuhiko (Frontiers in Physiology, 2022)
This study examined the effects of a resistance-type high-intensity interval training (RHIIT) matched with the lowest velocity that elicited V̇O2peak (100%vV̇O2peak) in well-trained kayak sprint athletes. Responses in cardiac structure and function, cardiorespiratory fitness, anaerobic power, exercise performance, muscular strength, and hormonal adaptations were examined. Male kayakers (n=24, age: 27±4 years) were randomly assigned to one of three 8-wk conditions (N=8): (RHIIT) resistance training using one-armed cable row at 100%vV̇O2peak; paddling-based HIIT (PHIIT) six sets of paddling at 100%vV̇O2peak; or controls (CON) who performed six sessions including 1-hour on-water paddling/sessions at 70-80% maximum HR per week. Significant increases (p<0.05) in V̇O2peak, vV̇O2peak, anaerobic threshold, maximal cardiac output, resting stroke volume, left ventricular end-systolic dimension, 500-m paddling performance were seen pre- to post-training in all groups. Change in V̇O2peak in response to PHIIT was significantly greater (p=0.03) compared to CON. Also, 500-m paddling performance changes in response to PHIIT and RHIIT were greater (p=0.02, 0.05, respectively) than that of CON. Compared with pre-training, PHIIT and RHIIT resulted in significant increases in peak and average power output, maximal stroke volume, end-diastolic volume, ejection fraction, total testosterone, testosterone/cortisol ratio, and 1000-m paddling performance. Also, the change in 1000-m paddling performance in response to PHIIT was significantly greater (p=0.02) compared to that of CON. Moreover, maximum strength was significantly enhanced in response to RHIIT pre- to post-training (p<0.05). Overall, RHIIT and PHIIT similarly improve cardiac structure and hemodynamics, physiological adaptations, and performance of well-trained kayak sprint athletes. Also, RHIIT enhances cardiorespiratory fitness and muscular strength simultaneously.